1999
DOI: 10.1080/03075079912331380168
|View full text |Cite
|
Sign up to set email alerts
|

Markets and motivation in part-time postgraduate education

Abstract: Recent policy in higher education in many countries has had a number of elements which are broadly economic. Current British policies emphasise the relationship of higher education to the economy, reflecting human capital theory, and competition between institutions, reflecting notions of the 'market'. The 1997 UK Government White Paper on higher education introduced an explicit price mechanism--tuition fees payable by students--into the full-time undergraduate system. The article reports the results of a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Collis (1996) describes professional learners as self-directed learners who focus their learning on a specific field which is of direct and immediate relevance to their work. Similar observations come from findings by Pratt, Hillier and Mace (1999), where postgraduate students' priorities were to upgrade their theoretical knowledge in order to inform professional practice.…”
Section: Skillssupporting
confidence: 76%
“…Collis (1996) describes professional learners as self-directed learners who focus their learning on a specific field which is of direct and immediate relevance to their work. Similar observations come from findings by Pratt, Hillier and Mace (1999), where postgraduate students' priorities were to upgrade their theoretical knowledge in order to inform professional practice.…”
Section: Skillssupporting
confidence: 76%
“…But student-customers cannot meaningfully be asked about fitness for use because they haven't begun to use the product. If every student in a university studies every subject with an eye to his or her future employment -which is also not true because, as research indicates, even students in professional Masters programs don't do that (Pratt et al 1999) -then the time factor intrudes, as it does with cars and whitegoods and other major purchases. The student won't know until some time after graduation how good the product is.…”
Section: Has the Product Been Delivered?mentioning
confidence: 93%
“…In one study it was found that students do not behave like rational consumers when deciding which postgraduate course to study. 18 One would assume that potential postgraduate students would obtain information of sufficient quantity and Rudd found that postgraduate research students tended to stay at the institution of their first degree because of its reputation; they liked the way graduate education was organised there; the institution was familiar to them; it was easy to stay where they were; and because of family or personal commitments. 20 Students who opted to go elsewhere were attracted by the reputation of the institution, department or academic staff.…”
Section: Examination Of the Buying Process For Postgraduatesmentioning
confidence: 99%